2014
DOI: 10.1371/journal.pone.0093854
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Resilience of Late Holocene Coastal Subsistence System in Southeastern South America

Abstract: Isotopic and molecular analysis on human, fauna and pottery remains can provide valuable new insights into the diets and subsistence practices of prehistoric populations. These are crucial to elucidate the resilience of social-ecological systems to cultural and environmental change. Bulk collagen carbon and nitrogen isotopic analysis of 82 human individuals from mid to late Holocene Brazilian archaeological sites (∼6,700 to ∼1,000 cal BP) reveal an adequate protein incorporation and, on the coast, the continua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
29

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 85 publications
(104 reference statements)
9
66
0
29
Order By: Relevance
“…Recent studies, however, have yielded increasing evidence in terms of demography, social organization, and long-term territorial stability for the presence of more complex communities based primarily in highly productive estuarine and lagoon environments (DeBlasis et al 1998(DeBlasis et al , 2007Gaspar et al 2008). Zooarchaeological studies (Figuti and Klokler 1996;Klokler 2008) and isotopic analyses of human bone (Colonese et al 2014) have shown that the diet of these groups relied predominantly on fishing, supplanting the deep-rooted idea of a simple nomadic shellfish-gathering economy. Indeed, bone artifacts from sambaquis are compatible with net and hook fishing technologies (Figuti and Klokler 1996).…”
Section: Sambaquismentioning
confidence: 99%
“…Recent studies, however, have yielded increasing evidence in terms of demography, social organization, and long-term territorial stability for the presence of more complex communities based primarily in highly productive estuarine and lagoon environments (DeBlasis et al 1998(DeBlasis et al , 2007Gaspar et al 2008). Zooarchaeological studies (Figuti and Klokler 1996;Klokler 2008) and isotopic analyses of human bone (Colonese et al 2014) have shown that the diet of these groups relied predominantly on fishing, supplanting the deep-rooted idea of a simple nomadic shellfish-gathering economy. Indeed, bone artifacts from sambaquis are compatible with net and hook fishing technologies (Figuti and Klokler 1996).…”
Section: Sambaquismentioning
confidence: 99%
“…By modifying their diet, populations can offset the overexploitation of specific resources, but also increase their resilience. Indeed, HG are often characterized as resilient because of their diverse diet (Bender 1978) and flexible social organization (Colonese et al 2014). …”
Section: Parameter 2: Economic Resourcesmentioning
confidence: 99%
“…Estudos zooarqueológicos e isotópicos deixam pouca dúvida acerca da importância dos recursos aquáticos na subsistência dos grupos sambaquieiros (FIGUTI, 1992;KLÖKLER, 2008;COLONESE et al, 2014). Os sambaquis aparecem no registro arqueológico da região desde aproximadamente 7.500 anos aP, quando o Nível Médio do Mar (NMM), em ascensão, atingiu o atual zero pela primeira vez no Holoceno.…”
Section: Introductionunclassified